2016
DOI: 10.15253/2175-6783.2015000100010
|View full text |Cite
|
Sign up to set email alerts
|

Main nursing diagnoses in hospitalized elderly people who underwent urological surgery

Abstract: Objective: to identify the main nursing diagnoses in the elderly during postoperative period of urologic surgeries. Methods:Cross-sectional and quantitative study conducted in a urological unit. Data collection was conducted through physicalexaminations and consultation to medical records. One hundred senior citizens who were hospitalized at the institutionparticipated in the study. Results: The most frequent urological surgical procedures were: transurethral resection of theprostate (27 %) and open prostatect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…Finally, the majority of the diagnoses and consequently of nursing care were determined in physiological health standards and few in psychosocial standards, a result that corroborates a study carried out in Dutch hospitals (14) and also in a study carried out in a Brazilian hospital with urological patients (15) .…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the majority of the diagnoses and consequently of nursing care were determined in physiological health standards and few in psychosocial standards, a result that corroborates a study carried out in Dutch hospitals (14) and also in a study carried out in a Brazilian hospital with urological patients (15) .…”
Section: Discussionsupporting
confidence: 82%
“…For the surgical patient, inform and guide him to surgical prepare procedures, evaluate the patient's evolution conditions on post-surgery, clarify doubts and provide individualized assistance can contribute to anxiety decrease of the patient and for the strengthen of bonds between nursing team and patient (6) . Studies that investigate the relation between patient expectation and nursing care, demonstrated that most of the patients that evaluated nursing care as bad, reported communication failure and lack of adequate information about health, disease and treatment conditions as the main cause of dissatisfaction (4,(11)(12) .…”
Section: Discussionmentioning
confidence: 99%
“…When referring to radical prostatectomy, the nursing team's performance becomes even more relevant, since there are a lot of expectations and doubts by the patient regarding their recovery (5)(6) . Prostate cancer is one of the most diagnosed malignant neoplasms in men worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nesse contexto de espera e ansiedade que envolve o processo cirúrgico, os familiares também estão intimamente envolvidos e compartilham com o paciente seus sentimentos e incertezas, tornando o manejo dessa situação ainda mais complexa para a equipe de saúde, visto que esses momentos são presenciados de perto por ela, pois está presente desde os cuidados pré-operatórios. A equipe multiprofissional necessita estar ciente do quadro clínico do paciente, mas também precisam saber ouvir, apoiar e auxiliar o paciente a compreender e enfrentar a situação vivenciada [14][15][16]. Ações educativas desenvolvidas no período perioperatório em um hospital universitário...| 16 Rev.…”
unclassified